Alloying effect of Mg on microstructure and mechanical properties at 300 °C of Al–5Cu–1Mn–0.5Ni heat-resistant alloy - Jinlong Chen; Jianmei Zhang; Honglei Shen; Hengcheng Liao; Hualong Li (Materials Research Express, 2021)
The effect of Mg alloying on microstructure and mechanical properties at 300 °C of Al–5Cu–1Mn–0.5Ni heat-resistant aluminum alloy was investigated by microstructure observation and tensile test. Alloying with 0.5 wt%Mg addition considerably increases the yield strength at 300 °C of samples at as-cast, as-solutionized and as-aged states. It also greatly enhances the strengthening effects from solution and ageing treatments, however, simultaneously, decreases the elongation greatly. During the solidification process of the alloy with Mg addition, a great amount of whisker-like Al–Cu–Mg compound phase is formed at the eutectic boundary zones in the form of ridge configuration, which is determined as AlCuMg intermetallic compound by TEM. During the solution treatment, this whisker-like AlCuMg phase is completely dissolved into Al matrix that leads to a remarkable rise in the increment of yield strength at 300 °C by solution strengthening. The alloying of Mg has a significant influence on the precipitation behavior during the ageing treatment, for examples, promoting the formation of finer θ ′′ particles and a great number of Cu–Mg atomic clusters. During high temperature tensile test, theses clusters evolve into fine cube-like Al _5 Cu _2 Mg particles with orthorhombic structure. It is the significant microstructure evolution induced by alloying of Mg that leads to the great rise in yield strength at 300 °C. Addition of Mg in Al–Cu–Mn–Ni alloy dose not lead to the formation of meta-stable or stable S phase, but whisker-like AlCuMg and cube-like Al _5 Cu _2 Mg compounds are determined by TEM.